ASSESSING THE CONTRIBUTION OF NIGERIAN MEDIA TO SOCIAL DEVELOPMENT THROUGH NATIONAL PLANNING - Nwosu, Emeka Ugochukwu (International Research Journal of Arts and Communication, 2025)
The focus of this research is to take a review of the National Development Plans of Nigerian government, 1975 to 1980 and articulate its concept of social development and the level in which the media has been assimilated in the implementation of the policies. It therefore, explores the concepts of media, development, development planning and social development in Nigeria. It in adopts the empirical research approach to evaluate the components, achievements and failures of the Third National Development plan with generalizations to cover subsequent development plans in Nigeria. A survey of the views of residents of Akwa Ibom State, South South, and Nigeria is taken as a unit of the entire country. Responses of 300 residents are drawn from the three senatorial districts and a statistical percentage of views on each of the research questions are assessed. Recommendations are that if development plans are to achieve expected ends, the policy makers must take adequate involvement of the media to disseminate the needed information, accept a private sector driven national development plan, and institute an entirely comprehensive development plan with regulating models under the control of experts, while future development plans require the setting up of meaningful goals.